Oorreding in 1 Korintiërs 1:10-17 - Snyman, AH (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
Persuasion in 1 Corinthians 1:10-17 The approach followed in this article differs from that of researchers, who use rhetorical models from outside to analyze a text, or who regard only a few stylistic techniques as rhetoric. The analysis is done in terms of what is called a “grounded theoretical approach”. This approach is briefly summarized, followed by a description of the rhetorical situation of the letter and a systematic analysis of these seven verses in order to determine its persuasive force. It is argued that these verses are an integral part of Paul’s rhetorical strategy, constructed from the text itself and aimed at persuading the Corinthians to be united by setting aside the reasons for their internal differences. The conclusion is that a text-centred approach with its focus on the functional aspects of the text, provides a good (or even better) alternative to existing approaches, with their focus on the formal aspects of the text.